2015
DOI: 10.1002/2015ja021579
|View full text |Cite
|
Sign up to set email alerts
|

How the IMF By induces a By component in the closed magnetosphere and how it leads to asymmetric currents and convection patterns in the two hemispheres

Abstract: We used the Lyon‐Fedder‐Mobarry global magnetohydrodynamics model to study the effects of the interplanetary magnetic field (IMF) By component on the coupling between the solar wind and magnetosphere‐ionosphere system. When the IMF reconnects with the terrestrial magnetic field with IMF By≠0, flux transport is asymmetrically distributed between the two hemispheres. We describe how By is induced in the closed magnetosphere on both the dayside and nightside and present the governing equations. The magnetosphere … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
163
2
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 100 publications
(182 citation statements)
references
References 65 publications
16
163
2
1
Order By: Relevance
“…The ratio indicates that for their step function IMF B y transition the final reconfiguration time should be close to 30 min. For this reason the conclusion in Tenfjord et al [] that the IMF B y induces a B y component on closed field lines on times scales of tens of minutes is in agreement with the empirical results of this study. Tenfjord et al [] found a shorter reconfiguration time on the dayside.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The ratio indicates that for their step function IMF B y transition the final reconfiguration time should be close to 30 min. For this reason the conclusion in Tenfjord et al [] that the IMF B y induces a B y component on closed field lines on times scales of tens of minutes is in agreement with the empirical results of this study. Tenfjord et al [] found a shorter reconfiguration time on the dayside.…”
Section: Discussionsupporting
confidence: 93%
“…In this scenario, the response on closed field lines is expected to be considerably slower compared to the more “direct” shear flows inducing B y and asymmetric foot points. This differs from the mechanism explained in Tenfjord et al [] in that it relies on tail reconnection in order to produce B y on closed field lines.…”
Section: Theorycontrasting
confidence: 64%
See 3 more Smart Citations